4-1BB co-stimulation further enhances anti-PD-1-mediated reinvigoration of exhausted CD39+ CD8 T cells from primary and metastatic sites of epithelial ovarian cancers. Issue 2 (16th December 2020) - Leem, Galam; Park, Junsik; Jeon, Minwoo; Kim, Eui-Soon; Kim, Sang Wun; Lee, Yong Jae; Choi, Seong Jin; Choi, Baekgyu; Park, Seongyeol; Ju, Young Seok; Jung, Inkyung; Kim, Sunghoon; et al.
Abstract : Background: Responses to immunotherapy vary between different cancer types and sites. Here, we aimed to investigate features of exhaustion and activation in tumor-infiltrating CD8 T cells at both the primary and metastatic sites in epithelial ovarian cancer. Methods: Tumor tissues and peripheral blood were obtained from 65 patients with ovarian cancer. From these samples, we isolated tumor-infiltrating lymphocytes (TILs) and peripheral blood mononuclear cells. These cells were used for immunophenotype using multicolor flow cytometry, gene expression profile using RNA sequencing and ex vivo functional restoration assays. Results: We found that CD39 + CD8 TILs were enriched with tumor-specific CD8 TILs, and that the activation status of these cells was determined by the differential programmed cell death protein 1 (PD-1) expression level. CD39 + CD8 TILs with high PD-1 expression (PD-1 high ) exhibited features of highly tumor-reactive and terminally exhausted phenotypes. Notably, PD-1 high CD39 + CD8 TILs showed similar characteristics in terms of T-cell exhaustion and activation between the primary and metastatic sites. Among co-stimulatory receptors, 4-1BB was exclusively overexpressed in CD39 + CD8 TILs, especially on PD-1 high cells, and 4-1BB-expressing cells displayed immunophenotypes indicating higher degrees of T-cell activation and proliferation, and less exhaustion, compared with cells not expressing 4-1BB. Importantly, 4-1BB agonistic antibodies further enhanced the anti-PD-1-mediated reinvigoration of exhausted CD8 TILs from both primary and metastatic sites. Conclusion: Severely exhausted PD-1 high CD39 + CD8 TILs displayed a distinctly heterogeneous exhaustion and activation status determined by differential 4-1BB expression levels, providing rationale and evidence for immunotherapies targeting co-stimulatory receptor 4-1BB in ovarian cancers.